AB0084 Serum Levels of Syndecan-1 and Organ Involvement in Systemic Lupus Erythematosus. (10th June 2014) - Fajardo-Robledo, N.; Diaz-Rizo, V.; Rocha-Muñoz, A.; Muñoz-Valle, J.; Gonzalez-Lopez, L.; Gamez-Nava, J.
Abstract : Background: Syndecan-1 is expressed on plasma cells surface and serum levels as reflect an activation of these cells. To date, a significant association between serum levels of syndecan-1with disease activity has been observed in a study evaluating patients with systemic lupus erythematosus (SLE). Nevertheless, to date there is a lack of information about. Objectives: Evaluate the association of syndecan-1 serum levels with disease activity and clinical variables Methods: We included 46 patients with SLE and were compared with 46 controls. Disease characteristics and treatments were assessed in patients with SLE. Serum levels of syndecan-1 and BLyS were obtained and correlated with clinical variables of the SLE patients. Results: Patients with SLE had a mean age of 42 years. From 46 patients with SLE, 30 (70%) had disease activity with a SLEDAI >3, and 21 (47%) had renal involvement. Patients with renal involvement had a trend to higher serum levels of syndecan-1 (129.7±80.4 vs. 87.1±65.4 respectively, p=0.07) Syndecan-1 correlated significantly with proteinuria (r=0.39, p=0.01). Also patients with cutaneous involvement had higher levels of syndecan-1 compared with patients without this involvement (126.5±81.3 vs. 96.2±69.2 respectively, p=0.01). Patients with higher levels of syndecan-1 also had a trend to higher doses of prednisone (r=0.28, p=0.07), and higher doses of mofetil mycophenolate (r=0.29, p=0.06) reflecting the treatment for a more severe disease activity. Conclusions: These results suggest that syndecan-1 serum levels are related with disease activity, particularly renal involvement. The potential role of this molecule should be evaluated in a prospective cohort study in order to identify if could be useful as a marker for different therapeutic outcomes in SLE. This project was financed by a grant of Instituto Mexicano del Seguro Social: FIS/PROT/G13/1202. References: Sanderson RD, Lalor P, Bernfield M. B lymphocytes express and lose syndecan at specific stages of differentiation. Cell Regul. 1989 Nov;1(1):27-35. Minowa, K., H. Amano, S. Nakano, S. Ando, T. Watanabe, Y. Nakiri, E. Amano, Y. Tokano, S. Morimoto, and Y. Takasaki, Elevated serum level of circulating syndecan-1 (CD138) in active systemic lupus erythematosus. Autoimmunity, 2011. 44(5) Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5962